Environmental Health and Toxicology: Immunomodulation Promoted by Endocrine-Disrupting Chemical Tributyltin - Ricardo Correia da Silva; Mariana Pires Teixeira; Luciana Souza de Paiva; Leandro Miranda-Alves (Toxics, 2023)
Tributyltin (TBT) is an environmental contaminant present on all continents, including Antarctica, with a potent biocidal action. Its use began to be intensified during the 1960s. It was effectively banned in 2003 but remains in the environment to this day due to several factors that increase its half-life and its misuse despite the bans. In addition to the endocrine-disrupting effect of TBT, which may lead to imposex induction in some invertebrate species, there are several studies that demonstrate that TBT also has an immunotoxic effect. The immunotoxic effects that have been observed experimentally in vertebrates using in vitro and in vivo models involve different mechanisms; mainly, there are alterations in the expression and/or secretion of cytokines. In this review, we summarize and update the literature on the impacts of TBT on the immune system, and we discuss issues that still need to be explored to fill the knowledge gaps regarding the impact of this endocrine-disrupting chemical on immune system homeostasis.